2022
DOI: 10.1002/adma.202107054
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Transition Metal‐Doped Hollow Cerium Tandem Nanozymes with Elaborately Regulated Multi‐Enzymatic Activities for Intensive Chemodynamic Therapy

Abstract: normal cells and is more sensitive to reactive oxygen species (ROS) elevation has attracted considerable attention. [1] From this perspective, ROS-generating approaches have been widely explored as a weapon to directly or indirectly kill cancer cells; these include photodynamic therapy (PDT), [2] radiodynamic therapy (RT), [3] sonodynamic therapy (SDT), [4] and chemodynamic therapy (CDT). [5] Promoted by recent advancements in nanochemistry and nanocatalysis, a variety of nanosystems with enzyme-like activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
145
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(146 citation statements)
references
References 63 publications
1
145
0
Order By: Relevance
“…The above investigations indicated a correlation between the structural defects of ceria nanozymes and their catalytic activity as peroxidase mimics [31,55,[96][97][98][99][100]. The high catalytic activity was found on the CeO 2 nanozymes featured with the high level of the surface Ce 3+ fraction and large surface area.…”
Section: Peroxidase-like Activitymentioning
confidence: 82%
“…The above investigations indicated a correlation between the structural defects of ceria nanozymes and their catalytic activity as peroxidase mimics [31,55,[96][97][98][99][100]. The high catalytic activity was found on the CeO 2 nanozymes featured with the high level of the surface Ce 3+ fraction and large surface area.…”
Section: Peroxidase-like Activitymentioning
confidence: 82%
“…The SOD family constitutes the first line of defense against ROS. The O 2 •− is dismutated by SODs to form H 2 O 2 , which can be decomposed into O 2 and H 2 O by CAT or GPXs [ 66 ]. Several enzymes, such as glutathione reductase and glucose-6-phosphate dehydrogenase, function as secondary antioxidant enzymes that enable GPX to function with cofactors (NADPH, GSH and glucose 6-phosphate) but not to act on ROS directly [ 67 , 68 ].…”
Section: Redox Homeostasis: the Biological Basis For Antioxidant Therapymentioning
confidence: 99%
“…Dong et al [ 126 ] reported a hollow mesoporous tandem nanozyme (denoted PHMZCO-AT) for T 1 -weighted MR/CT imaging-guided highly efficient catalytic treatment (Fig. 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 126 ]. Copyright 2022, Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim …”
Section: Introductionmentioning
confidence: 99%